Análise segmental e supra-segmental da língua Mundurukú - tronco Tupi - (:unkn) unknown (Museu Paraense Emílio Goeldi, 1996)
The Mundurukú language is the only one of a language family belonging to the Tupi trunk, spoken by a population of approximately 4,000 native speakers, divided into five areas of Alto Tapajós, municipality of Itaituba-P A. The analysis proposes a new interpretation for the segmental and supra-segmental phonology of the language, based on data provided by a native speaker (Lorival Mundurukú, 19 years old, Cururu Mission) in the period March-April/96. Together with the formation of the corpus, not only the segmental investigation was developed, but also the determination of the emetic tones, since the informant can whistle them perfectly. The results obtained have arguments to, in part, refute the analysis that existed until then (BRAUN & CROFTS, 1969), which claimed the existence of four tones - high tone, medium tone, low tone and a fourth tone related to laryngalization. After careful study, it was found that there are only two tones - high and low - as is typical of Tupi languages that are tonal. Laryngalization can distinguish, phonetically, a vocalic group from a similar group of normal vowels; however, it is not conditioned by the tones and, although it only occurs with the low tone, it is on the same level as the normal vowels receive. Further studies are needed, as this is a language of remarkable breadth in processes, not only phonological, but morphophonological and morphological as well.
Segmental and supra-segmental analysis of the Mundurukú language - Tupi trunk
Keywords: Língua Mundurukú; Tupi; CNPQ::CIENCIAS HUMANAS